2020
DOI: 10.21203/rs.2.17005/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High common childhood illnesses while treatment seeking behavior of mothers’/care givers’ was low at rural northwest Ethiopia

Abstract: Background: In most developing countries, childhood illness and deaths are among the most challenging health issues. Most of these deaths were due to preventable causes including acute respiratory infections (ARI), diarrhea, and febrile illnesses. Thus, identification of determinants of childhood illness would help to guide strategic planning and prioritize interventions.Method: Community based cross-sectional study was conducted. A two-stage cluster sampling technique was used to select households and mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Based on the study setting, three of the studies were conducted in Addis Ababa [ 11 , 17 , 21 ], two in the Tigray region [ 18 , 42 ], seven in the Amhara region [ 20 , 22 , 23 , 25 27 , 37 ], seven in the Oromia region [ 15 , 32 – 35 , 38 , 43 ], one in the SNNP region [ 24 ], one in the Benishangul region [ 39 ], and four were conducted nationwide [ 16 , 36 , 40 , 41 ]. Regarding the illness category, fifteen studies were conducted by including all the three childhood diarrhea, fever, and respiratory tract infections at the same time [ 15 , 17 , 20 – 25 , 27 , 32 , 33 , 36 38 , 42 ], four were for diarrhea only [ 18 , 21 , 26 , 43 ], three were for fever only [ 34 , 35 , 39 ], and three were for ARI only [ 16 , 40 , 41 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the study setting, three of the studies were conducted in Addis Ababa [ 11 , 17 , 21 ], two in the Tigray region [ 18 , 42 ], seven in the Amhara region [ 20 , 22 , 23 , 25 27 , 37 ], seven in the Oromia region [ 15 , 32 – 35 , 38 , 43 ], one in the SNNP region [ 24 ], one in the Benishangul region [ 39 ], and four were conducted nationwide [ 16 , 36 , 40 , 41 ]. Regarding the illness category, fifteen studies were conducted by including all the three childhood diarrhea, fever, and respiratory tract infections at the same time [ 15 , 17 , 20 – 25 , 27 , 32 , 33 , 36 38 , 42 ], four were for diarrhea only [ 18 , 21 , 26 , 43 ], three were for fever only [ 34 , 35 , 39 ], and three were for ARI only [ 16 , 40 , 41 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Ethiopia, although signi cant achievements have been made under-ve child mortality is still high accounting 55 deaths per 1000 live births (2) And the top leading causes were infectious diseases mainly diarrheal disease (25%), pneumonia (21%) and malaria (26%) (3) Common childhood illnesses are communicable diseases which is responsible for considerable underve child morbidity and mortality particularly in low and middle-income countries across the world. Diarrheal disease, febrile illness and acute Respiratory infections are among the leading cause of childhood illnesses (4) To reduce under-ve child morbidity and mortality timely and appropriate healthcare-seeking behavior of caregivers' do have a signi cant contribution (5), despite that a large number of children still died before reaching health facilities due to delayed and inappropriate healthcare seeking(6). Hence WHO suggested that appropriate healthcare-seeking practice can effectively save the lives of children by 20%, particularly from an acute respiratory infection (7).…”
Section: Introductionmentioning
confidence: 99%